2014
DOI: 10.23986/afsci.8542
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of paper mulches in crop production —a review

Abstract: Mulching has become an important practice in modern field production. Plastics are the most widespread mulching materials, and especially black polyethylene is used almost everywhere due to its low price and proved positive results in production. Together with its still growing popularity, there is increasing concern about the environmental effects of using such vast amounts of plastics in agriculture without solutions for sustainable and safe disposal of the material. There have been several attempts to try t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 56 publications
2
54
0
4
Order By: Relevance
“…These findings suggest that PLM can act as an insulation layer and thereby dampen the day‐night fluctuation of soil temperatures. Consistent with our results, Moreno and Moreno (2008) reported lower soil temperature under biodegradable film mulch than under traditional polyethylene mulch and Kader (2016) and Haapala et al (2014) measured lower temperatures under paper mulches than under black plastic mulching or without mulching. It thus appears that light permeability and changes in soil temperature below PLM resemble those under other biodegradable films.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings suggest that PLM can act as an insulation layer and thereby dampen the day‐night fluctuation of soil temperatures. Consistent with our results, Moreno and Moreno (2008) reported lower soil temperature under biodegradable film mulch than under traditional polyethylene mulch and Kader (2016) and Haapala et al (2014) measured lower temperatures under paper mulches than under black plastic mulching or without mulching. It thus appears that light permeability and changes in soil temperature below PLM resemble those under other biodegradable films.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, whether the effects of mulching on soil temperature are beneficial for the growth of crop plants – and also on seed germination and seedling growth of weeds – depends on the climate and plant type. In some regions, farmers should lower and in others increase soil temperatures for a higher yield (Haapala et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have recently analysed the agronomic and environmental performance of paper mulch (Martin-Closas et al, 2003;Moreno et al, 2013;Haapala et al, 2014), polyethylene with additives for degradation or biodegradable films (Filippi et al, 2011;Saraiva et al, 2012;Benincasa et al, 2014). By conducting field experiments, these studies showed that these potential substitutes of conventional films offer the advantage of degrading into non-toxic components.…”
Section: Introductionmentioning
confidence: 99%
“…Black polyethylene mulch (BPM) has been widely used in production of fresh-market field tomatoes. Polyethylene have excellent mechanical properties, light weight and relatively low price 3 . Beneficial responses of tomatoes to BPM include higher yield, earlier production and better fruit quality.…”
Section: Introductionmentioning
confidence: 99%